Investigation of Dissipation, Adsorption, Degradation, and Leaching of Triazophos Pesticide in Various Soils. (26th May 2016) - Bajeer, Muhammad Ashraf; Mallah, Muhammad Ali; Sherazi, Syed Tufail Hussain; Bhanger, Muhammad Iqbal; Nizamani, Shafi Muhammad
Abstract : This study concerns the investigation of dissipation, adsorption, and degradation of triazophos in different soils from Pakistan. These processes help in the disappearance of pesticide from the environment. Gas chromatography was used for dissipation and adsorption analysis while for degradation study mass spectrometer was used in addition of gas chromatography (GC-MS). The dissipation rate of triazophos in three different soils was 90% over 30 days with average half-life of 9.059 days. From dissipation study it was inferred that rate is variable in each soil due to climatic changes, soil nature and soil-pesticide interactions. Adsorption experiment has revealed that the adsorption of this pesticide to soil follows the pseudo first order kinetic model with rate constant value of 0.479/h and Freundlich isotherm with adsorption capacity of 1.832 mol/g. Degradation study has displayed two major metabolites, one is phosphorothioic acid, S-[2-[(1-cyano-1-methylethyl) amino]-2-oxoethyl] O, O-diethyl ester at retention time of 9.136 and the other is sulfotep at 14.304 min. The leaching potential of triazophos was also calculated from its half-life and organic carbon content present in soil which was 1.688 representing it as non leacher pesticide.